Microstructures, phase and mechanical characterisation of Al2O3-ZrO2-TiO2 coating produced by atmospheric plasma spraying - Cynthia Sin Ting Chang; Marcus Wyss; Michal Andrzejewski; Geoffrey Darut; Lukas Graf; Vladimir Novak; Margie Olbinado; Susanne Erpel; Alexander Vogel; Simon Bode; Michael de Wild; Armando Salito (Open Ceramics)
The microstructure, crystallographic phases, and mechanical properties of a newly developed Al2O3 – TiO2 – ZrO2 ternary ceramic coating were characterized. The coatings were produced by atmospheric plasma spraying as a preblended powder on Ti-6Al-4 V substrates using the new generation of the Debye-Larmor cascaded plasma torch. The 400 μm thick as-sprayed ternary ceramic coating is compact and neither delamination nor inter-/trans-granular cracks were found. The coating consists of single phase α-Al2O3, monoclinic m-ZrO2, and a nanocrystalline dual phase structure of α-Al2O3 and m-ZrO2. Ti is either present as ZrTiO4 or as solute in the dual phase. Cracking from the tip of the indent is rare and delamination was not observed after the progressive scratch test. The coating has potential in high wear applications for example in medical devices.